2011
DOI: 10.1038/modpathol.2011.63
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy patterns and prognosis in uveal melanomas

Abstract: Autophagy is a self-degradation mechanism by which cells recycle their own cytoplasmic constituents. It has been claimed that, under certain conditions, such a process may be associated with tumor progression. In this study, the autophagic activity was investigated in a series of 99 uveal melanomas after immunohistochemical staining for the autophagy-associated proteins MAP1LC3A and BECN1, most commonly known as LC3A and Beclin 1, respectively. These were assessed in parallel with the hypoxia-inducible factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 55 publications
1
39
1
Order By: Relevance
“…As previously reported (39), no association between Beclin 1 expression and patients' survival was noted. This notion however is in contrast with our earlier findings in colorectal carcinomas (41) and in uveal (42) and cutaneous (43) melanomas, where Beclin 1 expression showed a biphasic correlation with prognosis, as well as with the worse prognosis of the highly Beclin 1-positive endometrioid carcinomas (44). Then again, Beclin 1 expression showed no association with LC3A reactivity patterns in lung carcinomas, and this probably accounts for the aforementioned observation, as LC3A paranuclear expression and LC3A-positive SLS were associated with poor prognosis in lung carcinomas (4).…”
Section: Discussioncontrasting
confidence: 84%
“…As previously reported (39), no association between Beclin 1 expression and patients' survival was noted. This notion however is in contrast with our earlier findings in colorectal carcinomas (41) and in uveal (42) and cutaneous (43) melanomas, where Beclin 1 expression showed a biphasic correlation with prognosis, as well as with the worse prognosis of the highly Beclin 1-positive endometrioid carcinomas (44). Then again, Beclin 1 expression showed no association with LC3A reactivity patterns in lung carcinomas, and this probably accounts for the aforementioned observation, as LC3A paranuclear expression and LC3A-positive SLS were associated with poor prognosis in lung carcinomas (4).…”
Section: Discussioncontrasting
confidence: 84%
“…Upon induction of autophagy, LC3-I is subsequently conjugated with phosphatidylethanolamine to become LC3-II. Thus, the accumulated puncta and levels of cleaved LC3/LC3-I could correlate with autophagic activity, which has been used in several carcinomas, including breast carcinomas, malignant melanomas, pancreatic cancers, colorectal adenocarcinomas, non-small cell lung carcinomas, and uveal melanomas [9,27,[32][33][34][35][36]. Since p62 (SQSTM1) can be efficiently degraded by autophagy through direct binding to Atg8/LC3 on the autophagosome membrane, the expression of p62 inversely correlates with autophagic activity [33,37,38].…”
Section: Correlation Between the Decreased Expression Of Ulk1 And Thementioning
confidence: 96%
“…A recent study has shown that the induction of autophagy following ECM detachment is a prosurvival mechanism that prevents cells from undergoing anoikis (Fung et al, 2008). There is clinical evidence that hyperactive autophagy in melanoma and hepatocellular carcinoma leads to early metastasis and poor prognosis (Ding et al, 2008;Giatromanolaki et al, 2011).…”
Section: Ras and Autophagymentioning
confidence: 99%
“…As a result, accumulation of autophagosomes in tumour cells has been shown to correlate with clinical outcomes in cancer patients and this has raised the possibility of using autophagy markers as a prognostic tool in cancer treatment (Morselli et al, 2011;Giatromanolaki et al, 2011). For example, melanomas with higher levels of autophagosomes are less likely to respond to temozolomide and sorafenib treatment, which leads to a poorer clinical outcome in patients (Giatromanolaki et al, 2011). However, caution should be taken, because correlative studies of this kind rely on either the absence or presence of accumulated autophagosomes as a readout of autophagy.…”
Section: Autophagy As a Prognostic Toolmentioning
confidence: 99%